2015
DOI: 10.1530/rep-14-0567
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal exposure to xenoestrogens impairs the ovarian response to gonadotropin treatment in lambs

Abstract: Bisphenol A (BPA) and diethylstilbestrol (DES) are xenoestrogens, which have been associated with altered effects on reproduction. We hypothesized that neonatal xenoestrogen exposure affects the ovarian functionality in lambs. Thus, we evaluated the ovarian response to exogenous ovine FSH (oFSH) administered from postnatal day 30 (PND30) to PND32 in female lambs previously exposed to low doses of DES or BPA (BPA50: 50 mg/kg per day, BPA0.5: 0.5 mg/kg per day) from PND1 to PND14. We determined: i) follicular gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…Similarly, Chen et al (2015) recently demonstrated that AR-dependent DHT inhibits FSHRdependent FSH-induced GC proliferation in rats, consistent with previous studies (Pradeep et al 2002, Kayampilly & Menon 2012. However, FSH also reduces AR expression in GCs of rats (Lu et al 2009) and sheep (Rivera et al 2015). Conversely, AR and FSHR mRNA levels are positively correlated in GCs, and low and medium doses of AR-dependent testosterone increase FSHR expression in primates (Weil et al 1999, CatteauJonard et al 2008.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, Chen et al (2015) recently demonstrated that AR-dependent DHT inhibits FSHRdependent FSH-induced GC proliferation in rats, consistent with previous studies (Pradeep et al 2002, Kayampilly & Menon 2012. However, FSH also reduces AR expression in GCs of rats (Lu et al 2009) and sheep (Rivera et al 2015). Conversely, AR and FSHR mRNA levels are positively correlated in GCs, and low and medium doses of AR-dependent testosterone increase FSHR expression in primates (Weil et al 1999, CatteauJonard et al 2008.…”
Section: Discussionsupporting
confidence: 67%
“…Numerous reports have shown that the FSHR gene plays a key role in animal reproduction [25,26,27]. Chu et al found two mutation (g.681T>C and g.629C>T) in the 5' flanking region of the FSHR gene in Hu sheep and three novel mutations (g.200G>A, g.197G>A and g.98T>C) in Small Tail Han Sheep [12].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of such modifications on the overall estrous cycle was not determined in this study. Several other studies in sheep indicate that BPA developmental exposure (either in utero or neonatally) can alter the follicle dynamic (Rivera et al, 2011;Veiga-Lopez et al, 2014) or the ovarian response to FSH (follicular growth, FSH-induced estradiol secretion) in prepubertal animals (Rivera et al, 2015).…”
Section: Type Of Modificationmentioning
confidence: 97%